2022
DOI: 10.3390/ani12050572
|View full text |Cite
|
Sign up to set email alerts
|

Residual Feed Intake and Rumen Metabolism in Growing Pelibuey Sheep

Abstract: This study was carried out to evaluate the residual feed intake (RFI), volatile fatty acid (VFA) production and enteric methane (CH4) from growing Pelibuey sheep. In this case, 12 non-castrated Pelibuey with an initial average live weight (LW) of 21.17 ± 3.87 kg and an age of 3 months, were housed in individual pens and fed a basal diet with 16% of crude protein and 11 MJ ME for 45 days. Dry matter intake (DMI) was measured and the daily weight gain (DWG) was calculated using a linear regression between the LW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Recent studies have revealed microbial differences in the rumen between high and low RFI sheep ( Perea et al., 2017 ; Zhang et al., 2021 ; Arce-Recinos et al., 2022 ). More importantly, a microbial profile of 6 rumen microbial species could be used to rank the FE of sheep ( Ellison et al., 2019 ), but microbiota in both the rumen and intestinal tract should be considered, as the gastrointestinal tract microbiota are indispensable to the nutritive function of animals ( Perea et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed microbial differences in the rumen between high and low RFI sheep ( Perea et al., 2017 ; Zhang et al., 2021 ; Arce-Recinos et al., 2022 ). More importantly, a microbial profile of 6 rumen microbial species could be used to rank the FE of sheep ( Ellison et al., 2019 ), but microbiota in both the rumen and intestinal tract should be considered, as the gastrointestinal tract microbiota are indispensable to the nutritive function of animals ( Perea et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%